IFN-γ-mediated suppression of ANGPT2-Tie2 in endothelial cells facilitates tumor vascular normalization during immunotherapy - Cai, Zihao; Meng, Kelin; Yu, Taiyan; Xi, Yu; Yuan, Zhiwei; Wang, Xue; Wang, Congjian; Li, Lequn; Fu, Xiangning (Frontiers in Immunology, 2025)
IntroductionTumor angiogenesis is a critical biological hallmark of cancer, which involves multiple molecularly regulated signaling pathways, including the angiopoietin (ANGPT)-Tie2 and the vascular endothelial growth factor (VEGF) signaling pathways. Despite initial optimism, targeting tumor angiogenesis in the treatment of lung adenocarcinoma (LUAD) has been unsatisfactory. Currently, monotherapy with PD-1/PD-L1 inhibitors, or their combination with bevacizumab, is considered the standard therapeutic approach for LUAD. Recent studies have shown that immunotherapy suppresses tumor angiogenesis and facilitates vascular normalization. However, whether and how anti-PD-L1 therapy influences tumor vasculature remains unclear.MethodsTo investigate the impact of immunotherapy on the vasculature of LUAD, a mouse model of lung adenocarcinoma was established by subcutaneous implantation of Lewis lung carcinoma cells in vivo. The effects of different treatments on microvessel density and pericyte coverage were explored, and the expression of angiogenesis-related factors was analyzed. Furthermore, to explore the molecular mechanisms through which IFN-γ regulates tumor blood vessels during immunotherapy, we elucidated the specific mechanisms in vitro by means of techniques such as siRNA, ChIP, RT-qPCR, Western blot, and immunofluorescence. Finally, the effects of IFN-γ on the proliferation, migration, and angiogenic function of endothelial cells (ECs) were evaluated through CCK-8, Transwell, and HUVEC tube formation assays.ResultsEmploying a mouse model of LUAD, we demonstrated that PD-L1 blockade therapy inhibits tumor angiogenesis and normalizes vasculature in an IFN-γ-signaling-dependent manner. Notably, anti-PD-L1 therapy reduced Tie2 and ANGPT2 expression, and these effects were reversed by the JAK1/2 inhibitor. Mechanistically, we demonstrated that IFN-γ inhibited Tie2 and ANGPT2 expression in ECs, and suppressed ANGPT2 gene transcription through the AKT-FOXO1 signaling pathway. Interestingly, IFN-γ-mediated activation of STAT1 exerts negative regulation by directly binding to the promoter regions of the ANGPT2 and TEK genes. Functionally, IFN-γ limits the migration, proliferation, and tube formation of ECs.DiscussionIn conclusion, our results revealed a novel mechanism wherein IFN-γ-mediated inhibition of ANGPT2-Tie2 facilitates vascular normalization during immunotherapy in LUAD, which performs an essential function in the antitumor efficacy of immunotherapy.